2001
DOI: 10.1111/j.1095-8649.2001.tb02300.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased number of hybrids between benthic and limnetic three‐spined sticklebacks in Enos Lake, Canada; the collapse of a species pair?

Abstract: In July 1999, 49 three-spined sticklebacks were sampled from Enos Lake, Canada. Here a benthic/limnetic species pair is known to exist. In the sample, six individuals (12%) were of intermediate phenotype. These represent 17% of the 35 males in the sample. This large number of intermediates contrasts with the 1% in previous samples reported in 1984 and 1992 and may signal the collapse of the species pair. 2001 The Fisheries Society of the British Isles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 18 publications
2
37
0
Order By: Relevance
“…It corresponds with findings by Koeslag (1995) and Doebeli (1996) and see Bolnick and Fitzpatrick (2007), while others have found that some postzygotic isolation is necessary for speciation to happen and be maintained (Liou & Price 1994;Kelly & Noor 1996;Hostert 1997;Bolnick and Fitzpatrick 2007). Recent empirical work has also shown that the collapse of the species pair in Enos Lake, British Columbia (Kraak et al, 2001;Taylor et al 2006) has been accompanied by a loss of postmating isolation (Behm et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…It corresponds with findings by Koeslag (1995) and Doebeli (1996) and see Bolnick and Fitzpatrick (2007), while others have found that some postzygotic isolation is necessary for speciation to happen and be maintained (Liou & Price 1994;Kelly & Noor 1996;Hostert 1997;Bolnick and Fitzpatrick 2007). Recent empirical work has also shown that the collapse of the species pair in Enos Lake, British Columbia (Kraak et al, 2001;Taylor et al 2006) has been accompanied by a loss of postmating isolation (Behm et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…In nature reproductive isolation between benthics and limnetics is not complete either. Current estimates are that about 1-2% of adult fish are hybrids (McPhail 1992;Schluter & McPhail 1992, but see Kraak et al 2001); this is partly after selection (Gow et al 2007) and might well correspond to the production of about 4% hybrid offspring per generation. Of course, a value of τ = 0.5 allows for matings between benthics and limnetics, although rarely.…”
Section: The Models and Their Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a critical factor in the persistence of species pairs would appear to be conserving the current species composition (i.e., keeping invasive species out and conserving coastal cutthroat trout), rather than forming specific abiotic environmental management criteria. The collapse of the Enos Lake species pair into a hybrid swarm following the appearance of the American signal crayfish, Pacifastacus leniusculus (Kraak et al 2001;Taylor et al 2006), and extinction of the Hadley Lake species pair following the introduction of the brown bullhead (Hatfield 2001) are examples of the devastating impact that invasive species can have on stickleback species pairs. That being said, habitat loss and degradation is the number one threat to freshwater fishes in Canada, and the effect of invasive species is often compounded by habitat change (Dextrase and Mandrak 2006).…”
Section: Origin and Persistence Of Species Pairsmentioning
confidence: 99%